1997
DOI: 10.1002/(sici)1099-0739(199705)11:5<439::aid-aoc609>3.3.co;2-8
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of the Presence of Dimethylated, Trimethylated and "Refractory' Arsenic Compounds in Estuarine Salt‐marsh Halophytes

Abstract: Five species of halophytes were sampled in the salt marshes of the Tagus estuary, dried, ground and digested. They were further extracted with ethanol and the extracts passed through weak and strong cationic ionexchange resins, purified through TLC and submitted to pyrolysis mass spectrometry and HPLC-ICP/MS. Arsenic content and hydrideforming arsenic species were verified, in each step, by GF-AA and HG-QFAA. A high content of arsenic was found in the samples of halophytes studied, both di-and tri-methylated a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…While keeping this in mind, the discovery of arsenosugars in some of these plants (amounting to as much as 11% of extracted arsenic in Lemna minor) represents the first conclusive association of arsenosugars with higher terrestrial plants. Halophytes (salt marsh plants) were proposed to contain an arsenosugar, but no identification (i.e., comparison with known arsenosugar compounds) was carried out (25). Interestingly, only arsenosugars 1a and 1b are observed in the present study, which was also the case for other findings of arsenosugars in terrestrial environmental samples (3,11,26,27).…”
Section: Resultsmentioning
confidence: 47%
See 1 more Smart Citation
“…While keeping this in mind, the discovery of arsenosugars in some of these plants (amounting to as much as 11% of extracted arsenic in Lemna minor) represents the first conclusive association of arsenosugars with higher terrestrial plants. Halophytes (salt marsh plants) were proposed to contain an arsenosugar, but no identification (i.e., comparison with known arsenosugar compounds) was carried out (25). Interestingly, only arsenosugars 1a and 1b are observed in the present study, which was also the case for other findings of arsenosugars in terrestrial environmental samples (3,11,26,27).…”
Section: Resultsmentioning
confidence: 47%
“…Tetramethylarsonium ion (Tetra) was found in a vascular plant from Meager Creek (3), and its presence in some samples in the current study, albeit at very low levels, indicates a wider distribution than might otherwise be expected, considering its rare occurrence in sediments or waters (28,29). One other study has suggested the presence of tetra-alkylated arsenicals in plants, which was attributed to the uptake of similar compounds from the surrounding water (25). Tetramethylarsonium ion occurs in Drepanocladus sp.…”
Section: Resultsmentioning
confidence: 97%
“…The biochemical processes involved in osmoregulation provide a possible pathway for the production of AB. In most halophytes (salt tolerant plants), as well as some algae and halophytic bacteria, a number of compounds (e.g., glycine betaine and homobetaine) are produced in response to osmotic stress (26) to alter the osmotic gradient. It is possible that arsenic compounds such as arsenobetaine are produced through similar processes.…”
Section: Discussionmentioning
confidence: 99%
“…For the speciation of selenium, reversed-phase [10,11], ion exchange [12,13] and size exclusion [14] separation have been studied. Only a few works describe the simultaneous separation of arsenic and selenium species [15], as well as on-line hyphenation of CE with ICPMS for the determination of As and Se speciation [16,17].…”
Section: Introductionmentioning
confidence: 99%